LC–MS characterization, anti-kinetoplastide and cytotoxic activities of natural products from Eugenia jambolana Lam. and Eugenia uniflora - Celestina Elba Sobral de Souza; Ana Raquel Pereira da Silva; Janaina Esmeraldo Rocha; Maria Celeste Vega Gomez; Míriam Rolóm; Cathia Coronel; José Galberto Martins da Costa; Manoel L.C. Netto; Larissa A. Rolim; Henrique Douglas Melo Coutinho (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To evaluate the trypanocidal, leishmanicidal and cytotoxic activity of Eugenia jambolana (E. jambolana) and Eugenia uniflora (E. uniflora) extracts and fractions. Methods: The products were characterized by LC–MS. Antiparasitic assays were performed and cytotoxicity was evaluated in fibroblastos. In vitro assays were performed using spectrophotometric evaluation. All assays were performed in thrice. Results: The results showed that the extracts and the tannic fraction from E. jambolana inhibited 100% of the epimastigote lines. The ethanolic extract was the most efficient in all concentrations tested against the three parasite strains. In the cytotoxicity assay the flavonoid fraction showed low toxicity. All E. uniflora samples showed cytotoxicity at the highest concentration tested, but the extract showed no toxic effect on the fibroblasts at the lowest concentration. The flavonoid and tannic fractions were more efficient against Leishmania braziliensis promastigotes compared to the extract. However, the extracts and the tannic fraction were more effective against Leishmania infantum strains. The effect on epimastigote cells was observed at all concentrations tested, with all E. uniflora samples. However, the samples were more effective at the highest concentration, where there was inhibition in 100% of the Trypanosoma cruzi strains. Conclusions: The species E. jambolana and E. uniflora presented antiparasitic activity against all tested parasite strains, indicating that these species can serve as an alternative therapy as they were efficient in the tests performed. The E. uniflora extract and the E. jambolana flavonoid fraction presented a low cytotoxicity, opening the floor for new biological studies.